2020
DOI: 10.25272/ijisef.693027
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of Muslim and Non-Muslim Customers in Papua Province Towards Islamic Banking

Abstract: In the past few decades, Islamic banking has gained popularity not only in Muslim countries but also in non-Muslim countries. This is due to the fact that the products and services provided by Islamic banking are not only intended for Muslims but also non-Muslims. As one of the largest Muslim population countries in the world, Indonesia has the potential to develop its Islamic banking. However, not all Indonesians have the same level of knowledge and perceptions about Islamic banking. Therefore, it will turn o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Knowledge encompasses all information that consumers have regarding various types of products and services, as well as additional knowledge linked to these items and services and information related to their functions as consumers (Rachmawati, 2018). Each person has a different level of Islamic financial literacy, including awareness of Islamic financial product characteristics (Pratiwi & Affandy, 2020). Several studies have been undertaken to examine the community's knowledge and opinions concerning Islamic banking (Muslichah & Sanusi, 2019;Pratiwi & Affandy, 2020;Rachmawati, 2018).…”
Section: Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge encompasses all information that consumers have regarding various types of products and services, as well as additional knowledge linked to these items and services and information related to their functions as consumers (Rachmawati, 2018). Each person has a different level of Islamic financial literacy, including awareness of Islamic financial product characteristics (Pratiwi & Affandy, 2020). Several studies have been undertaken to examine the community's knowledge and opinions concerning Islamic banking (Muslichah & Sanusi, 2019;Pratiwi & Affandy, 2020;Rachmawati, 2018).…”
Section: Knowledgementioning
confidence: 99%
“…Each person has a different level of Islamic financial literacy, including awareness of Islamic financial product characteristics (Pratiwi & Affandy, 2020). Several studies have been undertaken to examine the community's knowledge and opinions concerning Islamic banking (Muslichah & Sanusi, 2019;Pratiwi & Affandy, 2020;Rachmawati, 2018). Studies suggested looking into non-Muslims as they will be more vulnerable, and this will strengthen the variables towards the willingness to choose Islamic microfinance (Utamy & Widhiastuti, 2020).…”
Section: Knowledgementioning
confidence: 99%